Distribution and source identification of nitrogen and phosphorus in aerosols in the Qinhuangdao coast, north China. (1st August 2020) - Yu, Limin; Ma, Xindong; Gao, Huiwang; Zong, Humin; Yao, Xiaohong; Lin, Zhongsheng; Zhang, Zhe; Zhang, Chong; Yao, Xiang; Zhang, Zhifeng
Abstract: Nitrogen and phosphorus in aerosols is an important source of nutrients in the coastal waters. To study all forms of composition and potential source of nitrogen and phosphorus in atmospheric particulates in the coastal waters of Qinhuangdao, 135 atmospheric aerosol samples were collected from August 2015 to August 2016. The result showed that the nitrogen in aerosols in the Qinhuangdao coastal area was more soluble (accounting for 91.7%), while phosphorus was more insoluble (62.3%). The same seasonal variation of nitrogen and phosphorus components was discovered, with the highest concentration in winter and the lowest in summer. Frequent dust and haze weather processes have a significant impact on the nitrogen and phosphorus species in aerosols. The concentrations of soluble nitrogen and phosphorus increased more significantly in haze days, while insoluble nitrogen and phosphorus increased more significantly in dust days. Both weather processes may aggravate the phosphorus limitation in the coastal waters of Qinhuangdao. Quantitative analysis of potential sources area indicated that Beijing–Tianjin–Hebei, Mongolia, Inner Mongolia contributed the most to the atmospheric nitrogen and phosphorus in Qinhuangdao coastal area. The total contribution of these three regions to atmospheric nitrogen and phosphorus pollution of Qinhuangdao were about 70%, which indicated that most of the atmospheric nitrogen and phosphorus in Qinhuangdao offshore come from the atmospheric pollutant transport channel in the northwest. Graphical abstract: Image 1 Highlights: The soluble nitrogen predominant in aerosols of Qinhuangdao coastal area compared with the insoluble nitrogen. Different with the nitrogen, the proportion of insoluble phosphorus was higher than the soluble phosphorus. The concentrations of soluble nitrogen and phosphorus increased more significantly in haze weather. Quantitative potential source analysis indicated that more than 70% nitrogen and phosphorus were from the adjacent areas.